2021
DOI: 10.3390/plants10071441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral and Organic Fertilization on desi and kabuli Chickpea (Cicer arietinum L.): Plant Growth and Production, Hydration Properties, Bioactive Compounds, and Antioxidant Activity

Abstract: Composting is a strategic technology to convert organic waste into environmentally friendly soil improvers, mitigating the pressure on landfills and contributing to sustainability. This research evaluates the effects of different doses of mineral/organic fertilizers on two chickpea types: desi and kabuli. A randomized block design with three replications and six conditions was adopted: non-fertilized control, two mineral fertilizations (M1, M2), and three organic fertilizations (B1, B2, B3). M1 and B1 provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…On the other hand, grain weight, which was the most determinant yield component, was more affected by genotype and water supply than starter N fertilization. This result is in accordance with a study conducted on the chickpea genotype Sultano [2], in which the authors observed that supplementary mineral N fertilization led to a non-significant increase in 100 seed weights.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, grain weight, which was the most determinant yield component, was more affected by genotype and water supply than starter N fertilization. This result is in accordance with a study conducted on the chickpea genotype Sultano [2], in which the authors observed that supplementary mineral N fertilization led to a non-significant increase in 100 seed weights.…”
Section: Discussionsupporting
confidence: 92%
“…Among legumes, in chickpea (Cicer arietinum L.) residual soil nitrogen appears to not affect nitrogen fixation, and a starter fertilization supply is frequently adopted [1]. Chickpea is a valuable source of proteins, dietary fiber, phytochemicals, and minerals, and as grains to cook or new flours used in addition or as an alternative to wheat [2,3]. Globulins represent the major fractions within storage proteins, including the cupin proteins convicilin, 7s vicilin, and 11s legumin, characterized by lower cysteine content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other findings are by Purushothaman et al (2014), Naderi et al (2021) and Basal and Szabó (2020) in chickpea are also in agreement with the findings of the present study. In contradiction, Pasqualone et al (2021) established a higher mean plant in Desi (79.39cm) than Kabuli (68.83cm) under various nitrogen treatments (30, 40, 100Kg N ha -1 ). Although Desi varieties expressed lower biomass than Kabuli, both gave low biomass under N0, but their maximum varied under various nitrogen treatments.…”
Section: Discussionmentioning
confidence: 81%
“…During the last decade, the interest in grain legumes has increased because they play an important nutritional role in the diet of millions of people in developing countries, but also because they represent a valuable source of protein, calcium, iron, phosphorus, and other minerals in the diets of vegetarians [1][2][3]. In particular, the chickpea (Cicer arietinum L.) is considered to be unique because of its potential health benefits, which include reducing cardiovascular, diabetic, and cancer risks, and because of its high protein bioavailability, biological value, and well-balanced amino acid profile [4].…”
Section: Introductionmentioning
confidence: 99%